Output containment analysis and design for high‐order linear time‐invariant swarm systems. (25th November 2013) - Dong, Xiwang; Shi, Zongying; Lu, Geng; Zhong, Yisheng
Summary Output containment analysis and design problems for high‐order linear time‐invariant swarm systems are dealt with. Firstly, output containment protocols are presented for leaders and followers, respectively, to partially assign the output motion modes of leaders and propel the outputs of followers to converge to the convex hull formed by the outputs of leaders. Then, output containment problems for swarm systems are transformed into stability problems, and sufficient conditions for swarm systems to achieve output containment are proposed. Moreover, an approach to determine the gain matrix in the protocol for swarm systems to achieve output containment is given, which has less calculation complexity. Finally, numerical simulations are presented to demonstrate theoretical results. Copyright © 2013 John Wiley & Sons, Ltd.